Incrementally non‐linear plasticity applied to rock joint modelling. (11th November 2011) - Duriez, Jérôme; Darve, Félix; Donzé, Frédéric‐Victor
SUMMARY Rock joint constitutive modelling is discussed through two new rock joint constitutive relations and a discrete numerical model. Regarding the constitutive relations, we emphasise the number of 'tensorial zones', that is, domains of constitutive incremental linearity; they involve four zones for the first (called 'quadrilinear') and an infinite number for the second one (called 'incrementally nonlinear'). Using these formulations, a large class of loading paths can be considered. Hardening through shearing and relations between the normal and tangential directions of the joint (e.g., dilatancy) can be described. Their predictive abilities are checked. Plastic features are included even if the relations are defined outside the elasto‐plastic formalism. These relations obey, hence, the physical evidence as the plastic limit criterion and flow rule. The flow rule is nonassociated, and the corresponding link with the nonsymmetry of the constitutive matrix is examined. Comparisons between the two relations and the discrete numerical model, that is, a direct numerical simulation, which is fundamentally different, also are discussed within the context of infilled rock joints. Copyright © 2011 John Wiley & Sons, Ltd.